2002
DOI: 10.1108/00070700210425688
|View full text |Cite
|
Sign up to set email alerts
|

Food safety and organic fruit demand in Italy: a survey

Abstract: Reports the first results of a study on how increased awareness of food safety can influence consumer behaviour regarding specific products. Looks into consumer attitudes towards organic apples by means of a survey conducted among customers of large retail outlets located in Emilia-Romagna (Italy). Analyses consumer attitudes toward organic food, studying the price/ quantity/quality relationship for this type of product. Consumers were directly interviewed at retail outlets, A questionnaire consisting of the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
49
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 4 publications
9
49
0
5
Order By: Relevance
“…In the literature it is found that consumers generally link organic foods to increased food safety in terms of an absence of GMOs and pesticide residues and to a lower degrees absence of artificial additives and preservatives (Yee, Yeung, & Morris, 2005;Canavari, Bazzani, Spadoni, & Regazzi, 2002;Honkanen, Verplanken, & Olsen, 2006), but the effect of food safety concern on the purchase of organic foods are mixed (Michaelidou & Hassan, 2008). In light of Michaelidou and Hassan's (2008) finding that concern about food safety issues are positively correlated with a positive attitude towards organic, but negatively correlated with purchase intentions, our results indicates that the effect of absence of GMOs and pesticide residues primarily works through confidence in the organic label.…”
Section: The Results Inmentioning
confidence: 99%
“…In the literature it is found that consumers generally link organic foods to increased food safety in terms of an absence of GMOs and pesticide residues and to a lower degrees absence of artificial additives and preservatives (Yee, Yeung, & Morris, 2005;Canavari, Bazzani, Spadoni, & Regazzi, 2002;Honkanen, Verplanken, & Olsen, 2006), but the effect of food safety concern on the purchase of organic foods are mixed (Michaelidou & Hassan, 2008). In light of Michaelidou and Hassan's (2008) finding that concern about food safety issues are positively correlated with a positive attitude towards organic, but negatively correlated with purchase intentions, our results indicates that the effect of absence of GMOs and pesticide residues primarily works through confidence in the organic label.…”
Section: The Results Inmentioning
confidence: 99%
“…Pangan organik diyakini lebih aman (Canavari et al, 2002) karena merupakan pangan alami yang dihasilkan tanpa menggunakan bahan kimia dan pupuk buatan (Connor dan Douglas, 2002). Produk pangan organik dihasilkan dari pertanian organik, suatu sistem produksi yang mempertahankan kesehatan tanah, ekosistem dan manusia (USDA 2010).…”
Section: Pendahuluanunclassified
“…3; it is wholesome, it remembers the past and it is fashionable (Schifferstein and Ophuis, 1998;Chinnici et al, 2002;Hill and Lynchehaun, 2002). From the side of the obstacles there are: high prices (Byrne et al, 1992;Tregear et al, 1994;Roddy et al, 1996;Magnusson et al, 2001;Zanoli & Naspetti, 2002), lack of availability (Zanoli and Naspetti, 2002), skepticism of certification boards (Ott, 1990;Canavari et al, 2002;Aarset et al, 2004), insufficient marketing (Roddy et al 1996;Chryssochoidis, 2000), satisfaction with traditional foods (Roddy et al, 1994) and cosmetic defects (Ott, 1990;Thompson and Kidwell, 1998). In addition, the research made by Paul and Rana (2012) underlines as the preference for organic foods is affected by demographic features, availability and by the comparison with inorganic food.…”
Section: The Eco-label Frameworkmentioning
confidence: 99%